2001
DOI: 10.1007/s002470100512
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity fetal lungs on MRI may suggest the diagnosis of pulmonary hypoplasia

Abstract: Low-intensity fetal lung on MRI imaging indicates pulmonary hypoplasia after 26 weeks' gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
53
2
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 0 publications
7
53
2
1
Order By: Relevance
“…5 Right pulmonary hypoplasia shows asymmetrically decreased right lung volume with abnormally low signal intensity. 6 In this case, diagnosis was made postnatally. We should have researched other importantˆndings after recognizing the right-sided heart.…”
Section: Discussionmentioning
confidence: 90%
“…5 Right pulmonary hypoplasia shows asymmetrically decreased right lung volume with abnormally low signal intensity. 6 In this case, diagnosis was made postnatally. We should have researched other importantˆndings after recognizing the right-sided heart.…”
Section: Discussionmentioning
confidence: 90%
“…The pathological findings of both lungs, ipsi-and contralateral to the herniated side, are the same in the rat model of CDH (23). In addition, Kuwashima et al have suggested that the high SI of HASTE represents a substantial amount of fetal lung fluid in the voluminous small airways and alveoli that are formed as the lung grows and comes to maturity (22). According to these previous reports, we considered it reasonable to note the SI of the contralateral lung.…”
Section: Discussionmentioning
confidence: 56%
“…Lung hypoplasia is histologically defined as a decrease in the number of airway generations and the number of alveoli (22). The pathological findings of both lungs, ipsi-and contralateral to the herniated side, are the same in the rat model of CDH (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low MRI intensity in T2-weighted image is thought to be a sign of pulmonary hypoplasia clinically, 17,18 and animal study also showed it. 19 However, the meaning of MRI signal intensity of the CDH lung remains controversial.…”
Section: Discussionmentioning
confidence: 95%